The mental as fundamental : new perspectives on panpsychism - Blamauer, Michael (Ontos Verlag, 2011)
A revival of panpsychistic considerations of the mind's place in nature has recently enriched the debate on the mind-body problem in contemporary philosophy of mind. The essays assembled in the present collection aim to supply a positive contribution to these considerations, providing new perspectives on panpsychism by shedding new light on its arguments and impacts as well as on its problems and theoretical challenges. Panpsychism is discussed as a position that understands consciousness as a truly fundamental feature of our reality - not only with respect to the human species, but also with.